1982
DOI: 10.1095/biolreprod27.1.183
|View full text |Cite
|
Sign up to set email alerts
|

Hypophysectomized Male Rats Treated with Polydimethylsiloxane Capsules Containing Testosterone: Eftects on Spermatogenesis, Fertility, and Reproductive Tract Concentrations of Androgens

Abstract: Spermatogenesis, reproductive luminal contents and androgen concentrations were examined in hypophysectomized male rats treated with 1 of 3 testosterone (T) dosages for 60-64 days and in sham-operated controls. Hypophysectomized rats treated with 2 cm long T implants showed normal mating but reduced fertility, while normal fertility was maintained in animals given 8 or 3 x 8 cm T. Spermatogenesis in the hypophysectomized groups treated with 2 cm T for 10 days was generally arrested at the spermatocyte stage, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 13 publications
2
19
0
Order By: Relevance
“…The difference between these views resides in the lack of quantitative data on germ cell numbers in different endocrinological states available at the time of the earlier review. Although this process is testosterone dependent, it is important to note that the levels of testosterone required within the testis are only 10-15% of those in normal testis; as described previously by us (16) and others (12,(40)(41)(42)(43), spermiogenesis can be supported with considerably lower intratesticular testosterone levels than those observed in normal rats.…”
Section: Elongated Spermatidsmentioning
confidence: 71%
“…The difference between these views resides in the lack of quantitative data on germ cell numbers in different endocrinological states available at the time of the earlier review. Although this process is testosterone dependent, it is important to note that the levels of testosterone required within the testis are only 10-15% of those in normal testis; as described previously by us (16) and others (12,(40)(41)(42)(43), spermiogenesis can be supported with considerably lower intratesticular testosterone levels than those observed in normal rats.…”
Section: Elongated Spermatidsmentioning
confidence: 71%
“…Earlier studies claimed that testosterone alone is capable of restoring spermatogenesis qualitatively in adults (Buhl et al 1982, Awoniyi et al 1992 without stimulating pituitary FSH (McLachlan et al 1994). Data from our laboratory demonstrated that FSH does not have the ability to rescue full spermatogenesis following chronic FSH and androgen action depletion in rats; however, mild increases in spermatogonia and flow on the effect of other germ cells up to pachytene spermatocytes have been observed (SM Ruwanpura, PG Stanton, DM Robertson, RI McLachlan, Y Makanji and SJ Meachem, unpublished observations).…”
Section: Long-term Studiesmentioning
confidence: 99%
“…Although testosterone may be the driving force for spermatogenesis in the adult testis, FSH is probably still required to some extent (see also below), for although androgens on their own can maintain spermatogenesis (Ahmad, Haltmeyer & Eik-Nes, 1973;Buhl, Cornette, Kirton & Yuan, 1982) they cannot maintain normal testicular weight, implying that sperm production is subnormal in this case. The next question is: do the actions of FSH and testosterone on the Sertoli cell vary according to the stage of the spermatogenic cycle?…”
Section: The Hormonal Control Of Spermatogenesismentioning
confidence: 99%